Entertainment facilities and the tourism industry: the Limbang, Sarawak context - Chua, Ervin Yi Wei; Kozlowski, Marek (Pertubuhan Arkitek Malaysia, 2020)
The entertainment industry has always contributed to the regeneration and economic development of cities. The purpose of this research is to ascertain the need of entertainment facilities in Limbang for tourists and residents and to determine their impact on the local economy. The methodology for this research includes field observations and collecting primary data through interviews involving the local and state authorities, residents and tourists in Limbang. A considerable amount of information supporting this study is based on literature review and secondary data sources. This research indicated that the entertainment facilities are essential in developing the tourism industry and improving the lifestyle of the locals. Besides, the study also helps decision-makers and town planners to understand how entertainment activities can regenerate decaying parts of cities and improve the socio-economic environment. One of the objectives of the Sarawak government is to transform Limbang into a tourist destination. Therefore, it is imperative to understand the process of allocating, planning, designing and developing entertainment facilities. The outcomes of this study revealed that Limbang could serve as a tourism destination, mainly targeting the citizens and foreign ex-pats of neighbouring Brunei.